PROGRAM PEMBERDAYAAN DALAM MENINGKATKAN PENDAPATAN NELAYAN DI DESA BUNONG KECAMATAN BINTAUNA KABUPATEN BOLAANG MONGONDOW UTARA - WATUNG, FRILIA FEREN; OGOTAN, MARTHA; LALOMA, ALDEN (JURNAL ADMINISTRASI PUBLIK, 2020)
This study aims to find out about the empowerment program in increasing the income of fishermenin Bunong Village, Bintauna Subdistrict, Bolaang Mongondow North Regency. This type of research used inthis research is qualitative descriptive research type. All data presented is in accordance with primary andsecondary data. Data collection techniques based on observation, interviews and documentation, dataobtained from various sources analyzed and made a conclusion. The problem in this study lies in the level ofincome and welfare of fishermen to the inability to utilize the potential of marine resources owned by Indonesia.The findings of this study indicate that the empowerment program in increasing the income of fishermen inBunong Village, Bintaunan Sub-district, Bolaang Mongondow North Regency is seen from the researchindicators namely enabling, empowering, and protecting can increase the income of fishermen by encouragingthe work spirit of fishermen through activities and assistance from empowerment programs such as capitalassistance, outreach, work equipment and motivation assistance, as well as workforce and facility training.The village government needs to collaborate more with the Maritime Affairs and Fisheries Office in conductingsocialization and training of workers in increasing the income of fishermen in Bunong Village, BintaunanSubdistrict, Bolaang Mongondow North Regency.Keywords : Empowerment Program, enhancement, income, fisherman